Atomistic Study of Lithium Ion Dynamics in Li12Si7. (20th December 2015) - Shi, Jianjian; Wang, Zhiguo; Fu, Y.Q.
Abstract: Lithium ion dynamics in crystalline lithium silicide Li12 Si7 were studied using density functional theory. Vacancy formation and diffusion of lithium ions showed a strong dependence on crystallographic sites of the lithium ions. The thirteen crystallographic lithium ions in the Li12 Si7 can be divided into three types based on their mobilities, and their typical diffusion energy barriers are 0.18, 0.36 and 0.52 eV, respectively. These crystallographic lithium ions take part in the fast diffusion process and are distributed within one dimensional column. The result agrees well with experimental report of the quasi-one dimensional fast diffusion channel in the Li12 Si7 .